Challenges in the Monitoring of Therapeutic Plasma Exchange during Acute Heparin-Induced Thrombocytopenia in Adults under ECMO - Gendron, Nicolas; Cavalie, Candice; Kantor, Elie; Provenchère, Sophie; Sonneville, Romain; Gkalea, Vasiliki; Bourrienne, Marie-Charlotte; Faille, Dorothée; Ajzenberg, Nadine (TH Open, 2024)
Therapeutic plasma exchange (TPE) has been proposed to remove heparin-induced thrombocytopenia (HIT) antibodies before planned thoracic surgery in patients with acute HIT and to allow brief re-exposure to heparin during surgery. In patients on extracorporeal membrane oxygenation (ECMO), simultaneous administration of TPE and alternative nonheparin anticoagulant therapies is challenging.We report 2 patients on ECMO with acute HIT who underwent repeated TPE to enable cardiothoracic surgery with the use of heparin. In both cases, serial monitoring of HIT antibody titer and heparin-induced platelet activation assay (HIPA) was performed. The effect of adding exogenous platelet factor 4 (PF4) in the HIPA was also tested.Negative anti-PF4/H IgG levels were achieved after 5 and 3 TPE sessions, respectively and patients could beneficiate from surgery with brief heparin re-exposure without any thrombotic complication. Negative HIPA results were obtained before negative anti-PF4/H IgG in one patient but remained positive in the other despite very low antibody titers. The addition of PF4 in HIPA led to more contrasted results for the two patients.Serial HIT screening including immunological and functional assays is necessary to closely monitor TPE in acute HIT patients on ECMO who require surgery. The addition of PF4 in HIPA could help detect clinically relevant platelet-activating antibodies and guide re-exposure to heparin.
Keywords: heparin-induced thrombocytopenia; therapeutic plasma exchange; platelet factor 4; platelet activation; extracorporeal membrane oxygenation